2019
DOI: 10.1029/2019jf005056
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical Modeling to Capture Seismic‐Shaking Patterns From Earthquake‐Induced Landslides

Abstract: We investigate earthquake-induced landslides using a geostatistical model featuring a latent spatial effect (LSE). The LSE represents the spatially structured residuals in the data, which remain after adjusting for covariate effects. To determine whether the LSE captures the residual signal from a given trigger, we test the LSE in reproducing the pattern of seismic shaking from the distribution of seismically induced landslides, without prior knowledge of the earthquake being included in the model. We assessed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 94 publications
(144 reference statements)
2
54
0
Order By: Relevance
“…In any region, landslide mapping is the fundamental task that must be completed for landslide susceptibility and hazard analyses. However, as landslide mapping requires time and effort, forward modelling and spatial analysis tools (e.g., see [33,34] for the Newmark mapping approach) have been developed to 'predict' landslide susceptibility more rapidly and without prior information on previous slope failures (as would be needed for regions hit by a severe storm or earthquake, for which a new or updated landslide susceptibility map should be rapidly created; see applications presented by [35,36]). Nonetheless, for a reliable and general (not event-based) landslide susceptibility assessment, landslide inventories provide a necessary control on such predicted susceptibility maps, as spatial analysis or forward modelling approaches cannot account for all region-specific information.…”
Section: Discussionmentioning
confidence: 99%
“…In any region, landslide mapping is the fundamental task that must be completed for landslide susceptibility and hazard analyses. However, as landslide mapping requires time and effort, forward modelling and spatial analysis tools (e.g., see [33,34] for the Newmark mapping approach) have been developed to 'predict' landslide susceptibility more rapidly and without prior information on previous slope failures (as would be needed for regions hit by a severe storm or earthquake, for which a new or updated landslide susceptibility map should be rapidly created; see applications presented by [35,36]). Nonetheless, for a reliable and general (not event-based) landslide susceptibility assessment, landslide inventories provide a necessary control on such predicted susceptibility maps, as spatial analysis or forward modelling approaches cannot account for all region-specific information.…”
Section: Discussionmentioning
confidence: 99%
“…As for the temporal scale, due to the large time-span, the detected temporal patterns may reflect more information due to longterm climatic variations rather than specific conditions. For this reason, we are planning to extend our spatiotemporal cluster analyses to more complex models, which can concurrently capture multivariate contributions featuring environmental effects, even at the latent level (Lombardo et al, 2018(Lombardo et al, , 2019a.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in probability can be captured through clustering analyses and various examples already exist in literature where this has been done at different spatial and temporal scales and via different analytical approaches. Notably, this type of application spans in many areas of natural hazards and have become mainstream in case of seismicity (e.g., Fischer and Horálek, 2003;Georgoulas et al, 2013;Varga et al, 2012;Woodward et al, 2018;Yang et al, 2019), joint sets and their orientation in rock outcrops (e.g., Tokhmechi et al, 2011;Zhan et al, 2017), groundwater monitoring (Chambers et al, 2015), wildfires (e.g., Orozco et al, 2012;Costafreda-Aumedes et al, 2016;Fuentes-Santos et al, 2013;Tonini et al, 2017), and landslides (e.g., Lombardo et al, 2018Lombardo et al, , 2019aTonini and Cama, 2019). In the specific case of flooding, Zhao et al (2014) used the projection pursuit theory to cluster spatial data and to build a dynamic risk assessment model for flood disasters.…”
Section: Introductionmentioning
confidence: 99%
“…We can interpret this setup as a random effects model of local variation on top of a broader trend (Lombardo et al . 2019). It can be shown that this combination returns yet another, additive Gaussian process (Rasmussen and Williams, 2006).…”
Section: Worked Examplesmentioning
confidence: 99%